Engaging undergraduate students in the Philippines in photonics research with a novel publication-driven online mentoring approach - Alarcon, Minella C (Archīum Ateneo, 2019)
This paper discusses a publication-driven, education-by-research model of engaging undergraduate students in Photonics/Optics/Physics research by requiring that all activities lead to journal publication within a year. It is based on a non-traditional university-industry collaboration arrangement that has the following unique features. First, it utilizes offshore-based alumni (in the USA) who are active in science and technology research as mentors for the students (in the Philippines) in conjunction with the university professor advisers. We adopt inexpensive online collaboration technologies to support their virtual presence. Second, our research topic “fuses” uniquely two separate courses of study, namely: (i) the traditional Special Relativity in Physics and (ii) the fast emerging Photonic Integrated Circuits (PICs), into an innovative research area we have called “Special-Relativity-on-a-Chip”. It has the flavor of physics education combined with a taste of the latest in PICs technology. It enhances the textbook understanding of Physics/Engineering while providing potential publication opportunities. Third, the research activities are focused mainly on modelling, simulations and design. These activities strengthen students’ learning since they concentrate on and master specific mathematical/Physics/programming skills. The goal of the project is to publish 5 journal papers, and so far, (i) 3 journal papers have been published, (ii) 1 international conference paper has been accepted for oral presentation, and (iii) 3 national conference papers have been submitted for publication. We also examine the existing research structure in the university to ensure the project’s success and share best practices.